OPTIMIZING THE USE OF AUTHENTIC MATERIALS IN THE WORD FORMATION PROCESS TO IMPROVE STUDENTS’ UNDERSTANDING IN THE ENGLISH MORPHOLOGY SUBJECT - Adha, Annisha Dyuli; Gusta, Wienda; Afersa, Mona (TELL - US JOURNAL, 2023)
The purposes of this research are to (1) determine students' abilities in using word formation by using authentic materials provided. The instrument used to determine the student's abilities is MAT (Morphological Awareness Test); and (2) to determine the type and process of word formation contained in the authentic materials. This study used descriptive qualitative method. The results of this research, based on the MAT used, showed that the students’ understanding towards word formation process increased with the mean score was 83,26.  Meanwhile, the types of word formation found in the authentic materials were compounding, derivation, inflection, conversion, abbreviation, back formation, and initialism.